Coronary artery dissection and acute myocardial infarction following blunt chest trauma - Bjørnstad, Johannes L (BioMed Central, 2009)
Blunt chest trauma might lead to cardiac injury ranging from simple arrhythmias to lethal conditions such as cardiac rupture. We experienced a case of initially overlooked traumatic coronary artery dissection which resulted in acute myocardial infarction (AMI). A high degree of suspicion is needed to diagnose this condition. Based on our case, we will give an overview of relevant literature on this topic. ECG, echocardiography, coronary angiography and cardiac enzymes are valuable tools in diagnosing this rare condition. The time span from coronary artery occlusion to revascularisation must be short if AMI is to be avoided.